Kinship honorifics and intercultural communication in German translations of things fall apart and arrow of God (2017)
This paper examines honorifics that mirror cultural and social standings and attitudes within the kinship system of the Igbo of Africa and, thereby, provides an understanding of the cultural constitution and identity of the society. Variations in kinship systems and terms across cultures create difficulty in the transfer of cultural knowledge through translation - instanced here with Igbo and German cultures. This difficulty, therefore, demands that a translator does a close reading of cultural narrative contexts of kinship honorifics usages to avoid misrepresentation of cultures and to achieve intercultural understanding.